Exploring Disease Manifestations and Influencing Factors in Acute and Chronic Hepatitis B - Napoleon Bellua Sam; Abena Serwaa Ofosu; Saeed Folorunsho Majeed (European Scientific Journal, ESJ, 2024)
Scope and Aims: The investigation into disease manifestations and influencing factors of both acute hepatitis B (AHB) and chronic hepatitis B (CHB) is relatively limited and with varied results. This study was to investigate the influencing factors and disease manifestations of AHB and CHB in a Ghanaian population, in order to come out with a control strategy.  Methods: A retrospective study was conducted on 569 admitted hepatitis B cases. Demographic data and disease manifestations were compared between AHB and CHB patients. Results: There was a significant difference in median age as well as hospitalization duration for AHB and CHB patients. The variations in age, gender, educational level and occupational distributions between AHB and CHB patients were statistically significant (P < 0.05). Fever, nausea, polydipsia, palpitation, anicteric, anorexia, itching were less common (P < 0.05), abdominal, jaundice and enlarged liver was more frequent (P < 0.05), aspartate aminotransferase, viral load, bilirubin, prothrombin time, partial thromboplastin time, HBeAg, albumin, abdominal ultrasound, globin levels were significantly higher (P < 0.05), and HBsAg and liver function test levels were significantly lower (P < 0.05) in CHB patients than in AHB patients. Logistic regression revealed that age, gender, occupation, educational level, and hospitalization duration were the influencing factors. Conclusion: The males, as well as the adult population, constituted a higher percentage of CHB patients with a significant association of higher prevalence of clinical and laboratory characteristics. Age, gender, occupation, educational level and hospitalization duration were established as influencing factors.